The genetics of non-syndromic hearing impairment in South Africa - Manyisa, Noluthando (Department of Clinical Laboratory Sciences, 2024)
Hearing impairment (HI) is a sensory disorder resulting in the partial or complete disability to perceive sound in the better-hearing ear. It is defined as the inability to hear better than 25dB in the better-hearing ear. Subsequently, it is considered disabling when a child cannot perceive sound better the 30dB, in the better hearing ear, and an adult cannot perceive sound better than 40dB, in the better hearing ear. Hearing impairment may result from genetic, environmental, or unknown factors. The connexin gene, GJB2, is the prevalent gene resulting in congenital HI in most children with European, North American, and East Asian ancestry. Apart from the founder mutations present in GJB2 in Morocco, Ghana and Senegal, the prevalent causative genes resulting in congenital HI in African populations are yet to be fully elucidated. Congenital Hearing impairment in South Africa (RSA), has been estimated to have an incidence rate of 5.5 per 1000 live births, which is 5 times higher than the birth incidence in high-income countries (approximately 1 to 2 per 1000 live births). Patients are generally diagnosed late with HI, at approximately 3 years old, and the most prevalent environmental factors associated with HI in RSA are middle ear infections, with several reports implicating ototoxicity as a cause of HI. Variants in connexin genes i.e. GJB2 associated with HI have been shown to be irrelevant in the Black South African populations, and the limited genetic studies have identified private mutations in selected families. However, the full extent of prevalent genes associated with HI in the South African populations is still to be investigated. Methods and results Through a systematic review, we investigated the state of HI research in South Africa was established. Though studies have been performed since the 1960s, the results showed that genetics of HI in South Africa was not well explored. Universal new-born hearing screening is ideal in detecting congenital HI, but it is currently not standard practice in the country. However, with the advent of modern technology, HI screening may be more accessible to patients through community health workers. Patients who fail the repeated screenings may then be referred for further audiometry testing. This may positively impact the identification of patients with HI and assist with the necessary interventions. We also collaboratively worked to establish the first disease ontology for HI to further allow standardised and harmonised language surrounding HI. This provides the scalability and interoperability of research going forward. It will allow for all stakeholders in HI research to use the same terminology when discussing HI. In order to address the dearth of genetics research regarding non-syndromic HI, patients presenting with putative genetic HI were recruited from schools of the deaf across South Africa and two hospitals in Cape Town. The patients were recruited along with their family members, both with and without HI, and their DNA was extracted from whole blood. Twenty-seven families segregating non-syndromic HI, consisting of 65 affected and 35 unaffected individuals were subjected to whole exome sequencing (WES). The HI was resolved in 20 families (74%), and pathogenic variants were identified in the genes: WFS1 (c.A2141), MITF (cT918A), ADGRV1(c.G564T, c.A17450G, c.A11298C), PDSS1(c.C641T, NEU1(c.C1069T, c.G754C), c.G727A), TBC1D24(c.G1514A), MYO15A(c.C1378T, TMPRSS3(c.205+6t>A), c.9303+5G>A, c.G6634A), USH2A(c.T9437A, c.G2990T, c.G101A), STRC(c.G225A, c.C4057T, c.G4655C, c.C4351T, c.G4403A), P2RX2(c.G1064A, c.C1187G), OTOG(c.C2525A, c.G3143A, c.G916A), LHFPL5(c.621delC), TRIOBP(c.C3133T, c.C4298T), SLC26A4(c.T94C, c.T716A), GJB2(c.35delG), REST(c.G1244C), CRYM(c.*6_*2delACAAA), CDH23(c.T1585C, c.G8230A), FGFR2(c.1297+10G>C), MYO7A(c.6255delC). The pathogenic variants presented 8 autosomal dominant alleles and 12 autosomal recessive alleles Five families presented with pathogenic or likely pathogenic variations associated with Usher Syndrome and the remaining 14 families presented with pathogenic variations associated with non-syndromic HI. One family presented with putative pathogenic variations in NEU1, which is a gene associated with Sialidosis. We specifically investigated, in greater detail, a dominant novel variation in REST, present in one family, which encodes a transcription factor, that was identified using whole exome sequencing. This gene was previously suspected to be associated with hearing impairment only once, in an American family. The variation was absent in the unaffected South African family members, unrelated patients, and unaffected controls. In vitro cell-based studies indicated that the variation results in the loss of nuclear exclusivity of REST. Luciferase assays indicated that the mutant was unable to repress the expression of one of its target genes, whereas the wild-type effectively inhibited the expression of the target. Conclusions This thesis successfully performed the following investigations: 1) development of the first Hearing Impairment Ontology worldwide, 2) review the genetic profile of HI in South Africa, 3) used WES to find known and novel variants in established HI genes, and 4) confirmed REST as a novel HI gene. Future work will focus on sequencing all the remaining samples and identifying their putative causative mutations. Further work includes feedbacking the results of the genetic testing to the patients and their families. The data will contribute to improving the HI-genes pairs' curation in Africa, and globally.